Efforts To Increase Students' Creativity Through The Tps (Think Pair Share) Cooperative Learning Model On The Phytagoras Theorem Principles In Class VIII SMP Negeri 2 Sipahutar - Tampubolon, Veronika (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
This research is motivated by the creativity of students of SMP Negeri 2 Sipahutar is still low. For this reason, this study aims to determine whether the TPS (Think Pair Share) type of cooperative learning model can increase students' creativity. This research is a classroom action research conducted in two cycles. The research location is SMP Negeri 2 Sipahutar. The subjects in this study were students of class VIII SMP Negeri 2 Spahutar T.P 2010/2011, totaling 31 people. The object under study is an effort to increase students' creativity through the TPS (Think Pair Share) type of cooperative learning model. The test consists of: Initial Test (before the action), Creative Thinking Test I (after cycle I) and Creative Thinking Test II (after cycle II). The data obtained before the action was taken, the average score from the initial test was 40.35 and only 9 students with scores above 60 and 26 students with scores below 60. After giving the first cycle of action, the results were 20 students who achieved a higher score. greater than 60 and 11 students who achieved a score below 60 with an average score of 65.84 creative thinking. Because the number of students who achieved a creative thinking score greater than 60 had not yet achieved classical completeness, the research continued to cycle II (the research was not successful). In the second cycle, there were 27 students (87.10%) who achieved a score greater than 60 and 4 students (12.90%) who had not achieved a score greater than 60 with an average score of 80.16 students' creative thinking. The classical increase from the creative thinking test I to the second creative thinking test was 22.58% with an average increase of 14.32. From the average score, it was found that there was an increase in student creativity from cycle I to cycle II. Based on the results of the research with two cycles, it can be concluded that cooperative learning type TPS (Think Pair Share) can increase students' creativity.